Loss of Cep72 affects the morphology of spermatozoa in mice - Chen, Zhen; Xu, Yating; Ma, Dupeng; Li, Changrong; Yu, Ziqi; Liu, Cong; Jin, Tingyu; Du, Ziye; Li, Zejia; Sun, Qi; Xu, Yumin; Liu, Rong; et al. (Frontiers in Physiology, 2022)
The centrosome regulates mammalian meiosis by affecting recombination, synapsis, chromosome segregation, and spermiogenesis. Cep72 is one of the critical components of the centrosome. However, the physiological role of Cep72 in spermatogenesis and fertility remains unclear. In this study, we identify Cep72 as a testis-specific expression protein. Although Cep72 knockout mice were viable and fertile, their sperms were morphologically abnormal with incomplete flagellum structures. Transcriptome analysis reveals significant differences in six genes (Gm49527, Hbb-bt, Hba-a2, Rps27a-ps2, Gm29647, and Gm8430), which were not previously associated with spermatogenesis. Overall, these results indicate that Cep72 participates in regulating sperm morphology and yet is dispensable for fertility in mice.